2022
DOI: 10.1155/2022/1251478
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Safety of the Tripterygium Glycoside Adjuvant Methotrexate Therapy in Rheumatoid Arthritis: A Systematic Review and Meta-Analysis

Abstract: Objective. This study aimed to systematically review the efficacy and clinical safety of different courses and doses of tripterygium glycoside (TG) adjuvant methotrexate (MTX) therapy in the treatment of rheumatoid arthritis (RA). Methods. Randomized controlled trials (RCTs) of TG adjuvant MTX therapy in patients with RA were retrieved from SinoMed, China Network Knowledge Infrastructure, WanFang Data, PubMed, Cochrane Library, and Embase from inception to September 30, 2021. The effects and clinical safety ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…There were 14 studies on Chinese herbal medicines, including two reviews on various Chinese herbal medicines as a pooled group ( 57 , 59 ), seven on Tripterygium willfordii Hook F extract (TwHF 2 ) (also known as leigongteng or thundergod vine) ( 51 , 53 , 56 , 60 , 63 , 64 , 66 ), and five on other specific medicines ( 52 , 54 , 55 , 61 , 62 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were 14 studies on Chinese herbal medicines, including two reviews on various Chinese herbal medicines as a pooled group ( 57 , 59 ), seven on Tripterygium willfordii Hook F extract (TwHF 2 ) (also known as leigongteng or thundergod vine) ( 51 , 53 , 56 , 60 , 63 , 64 , 66 ), and five on other specific medicines ( 52 , 54 , 55 , 61 , 62 ).…”
Section: Resultsmentioning
confidence: 99%
“…Monotherapy with TwHF extract showed an improved clinical response (ACR20) when compared with most DMARDs except cyclosporine A ( 53 ). Additionally, a combination of TwHF with methotrexate also showed improved disease activity when compared with placebo or other medications ( 56 ). With regard to other outcomes, TwHF, either as a monotherapy or a combination therapy with various DMARDs, demonstrated benefit for biomarkers, disease activity, and pain across most comparisons, although the impact on joint counts was mixed ( 51 , 56 , 60 , 63 , 66 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 2021 ; Geng et al. 2022 ). These results demonstrate that the incidences of liver dysfunction, amenorrhea, and leukopenia are low in the patients receiving TG, and the risks of these adverse effects are not remarkably increased along with the accumulated total dose of TG.…”
Section: Discussionmentioning
confidence: 99%
“… 2021 ; Geng et al. 2022 ). In recent years, some clinical trials have indicated that TG as an add-on treatment could improve the efficacy in comparison with H1-AH alone in adults with CU (Wei et al 2010 ; Xing and Feng 2017 ), and TG is recommended as the second-line treatment in the Chinese guideline for urticaria (CSD, CUR 2019 ).…”
Section: Introductionmentioning
confidence: 99%